Understanding endothelial dysfunction in diabetic cardiovascular complications using mass spectrometry-based proteomics - Banarjee, Reema; Sharma, Akshay; Bai, Shakuntala; Deshmukh, Arati; Kazi, Rubina; Kulkarni, Mahesh J. (Heart, 2016)

Methylglyoxal attenuates insulin signaling and downregulates the enzymes involved in cholesterol biosynthesis - Deshmukh, Arati B.; Bai, Shakuntala; Aarthy, T.; Kazi, Rubina S.; Banarjee, Reema; Rathore, Rajeshwari; Vijayakumar, M. V.; H. V. Thulasiram; Bhat, Manoj Kumar; Kulkarni, Mahesh J. (Molecular Biosystems, 2017)
Methylglyoxal (MG) is a highly reactive dicarbonyl known to be elevated under the hyperglycemic conditions of diabetes and is implicated in the development of diabetic complications. Therefore, the current study investigates the role of MG in exacerbating insulin resistance at the insulin signaling level, as well as its effect on the global proteomic level. By using insulin sensitive rat muscle cells (L6) and Chinese hamster ovary (CHO) cells stably expressing the insulin receptor (IR) and a glucose transporter fused with green fluorescent protein (GLUT4-GFP), we have observed that MG impairs insulin signaling, inhibits GLUT4 translocation and reduces glucose uptake. SWATH MS analysis, a label-free quantitative mass spectrometric approach, showed altered expression of 99 proteins out of 2404 identified in response to MG treatment. These proteins are mainly involved in stress response, protein folding and proteolysis. Some of the deregulated proteins such as thioredoxin 2, glutathione S transferase, T complex protein 1 subunit beta (tcbp1), heat shock protein 90 and E3 ubiquitin ligase were previously reported to be associated with either diabetes or insulin resistance. Interestingly, aminoguanidine (AMG), a potent dicarbonyl scavenger, restored the deleterious effects of MG. For the first time, we report that MG induces downregulation of enzymes involved in cholesterol biosynthesis such as acetyl-CoA acetyltransferase, hydroxymethylglutaryl-CoA synthase, farnesyl pyrophosphate synthetase, squalene monooxygenase, and lanosterol synthase. GC MS analysis for sterol metabolites corroborated the proteomic results; MG significantly reduced cholesterol production whereas AMG treatment restored cholesterol production to levels similar to the control. Thus, MG leads to primary defects in insulin signaling and cellular abnormalities at the proteomic and metabolic levels, both of which may contribute to the development of insulin resistance.

Proteomic study of endothelial dysfunction induced by Ages and its possible role in diabetic cardiovascular complications - Banarjee, Reema; Sharma, Akshay; Bai, Shakuntala; Deshmukh, Arati; Kulkarni, Mahesh J. (Journal of Proteomics, 2018)
Endothelial dysfunction is one of the primary steps in the development of diabetes associated cardiovascular diseases. Hyperglycemic condition in diabetes promotes accumulation of advanced glycation end products (AGEs) in the plasma, that interact with the receptor for AGEs (RAGE) present on the endothelial cells and negatively affect their function. Using Human umbilical vascular endothelial cells (HUVECs) in culture, the effect of glycated human serum albumin on global proteomic changes was studied by SWATH-MS, a label free quantitative proteomic approach. Out of the 1860 proteins identified, 161 showed higher abundance while 123 showed lesser abundance in cells treated with glycated HSA. Bioinformatic analysis revealed that the differentially regulated proteins were involved in various processes such as apoptosis, oxidative stress etc. that are associated with endothelial dysfunction. Furthermore, the iRegulon analysis and immunofuorescence studies indicated that several of the differentially regulated proteins were transcriptionally regulated by NF-kappa B, that is downstream to AGE-RAGE axis. Some of the important differentially regulated proteins include ICAM1, vWF, PAI-1 that affect important endothelial functions like cell adhesion and blood coagulation. qPCR analysis showed an increase in expression of the AGE receptor RAGE along with other genes involved in endothelial function. AGE treatment to HUVEC cells led to increased oxidative stress and apoptosis. This is the first proteomics study that provides insight into proteomic changes downstream to AGE-RAGE axis leading to endothelial dysfunction and predisposing to cardiovascular complications. Significance: Cardiovascular disease (CVD) is a major pathological outcome in diabetic patients and it is important to address ways that target its development before the onset. Elevated plasma AGEs in diabetes can affect endothelial function and can continue to show their effects even after blood glucose levels are back to normal. Since endothelial dysfunction acts as one of the initiating factors for the development of CVD, understanding how AGEs affect the endothelial cell proteome to cause dysfunction will provide insight into the mechanisms involved and aid designing new therapeutic approaches.

CD44, a predominant protein in methylglyoxal-induced secretome of muscle cells, is elevated in diabetic plasma - Bai, Shakuntala; Chaurasiya, Arvindkumar H.; Banarjee, Reema; Walke, Prachi B.; Rashid, Faraz; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2020)
Methylglyoxal (MG), a glycolytic intermediate and reactive dicarbonyl, is responsible for exacerbation of insulin resistance and diabetic complication. In this study, NIG-induced secretome of rat muscle cells was identified and relatively quantified by SWATH-MS. A total of 643 proteins were identified in MG induced' secretome, of which 82 proteins were upregulated and 99 proteins were downregulated by more than 1.3-fold in SWATH analysis. Further, secretory proteins from the dassical secretory pathway and nonclassical secretory pathway were identified using SignalP and SecretomeP, respectively. A total of 180 proteins were identified with SignalP, and 113 proteins were identified with SecretomeP. The differentially expressed proteins were functionallyannotated by KEGG pathway analysis using Cytoscape soft ware with plugin clusterMaker. The differentially expressed proteins were'sfound to he involved m various pathways like extracellular matrix (ECM) receptor interaction, leukocyte transendothelial migration, fluid shear tress and atherosclerosis, complement and coagulation cascades, and lysosomal pathway. Since the MG levels are high in diabetic conditions, the presence of MG-induced isecreted proteins was inspected `by profiling human plasma of healthy and diabetic subjects (n = 10 each). CD44, a predominant MG -induced secreted protein, was found to be elevated in the diabetic plasma and to have a role in the development of insulin resistance.

SWATH-MS based quantitative proteomics analysis to evaluate the antileishmanial effect of Commiphora wightii- Guggul and Amphotericin B on a clinical isolate of Leishmania donovani - Bar Routaray, Chinmayee; Bhor, Renuka; Bai, Shakuntala; Kadam, Nitin Suryakant; Jagtap, Surabhi; Doshi, Pooja Jignesh; Sundar, Shyam; Sawant, Sangeeta; Kulkarni, Mahesh J.; Pai, Kalpana (Journal of Proteomics, 2020)
The present study provides comprehensive proteomics analyses of the response of L. donovani parasite to pharamacological stress in vitro. Identification of differentially expressed proteins with associated molecular functions and metabolic pathways, clearly provides an insight into the potential mechanism of the antileishmanial effects as well as a comparative response of the parasite to Guggul and AmB. Treatment of parasite with AmB results in an enhanced modulatory mechanism to counteract the drug induced stress which may have contributed to relapse. In the case of Guggul treatment, an effective antipromastigote activity was observed, which is being reported for the first time. Thus, a deeper understanding of the molecular pathways in the Leishmania parasite in response to pharmacological stress would help in designing novel and effective strategies in targeting the key molecules essential for parasite survival. It will also help in screening of new lead molecules targeting these vital pathways which could be used as an adjunct therapy along with the limited repertoire of antileishmanial drugs.

SWATH-MS based quantitative proteomics analysis to evaluate the antileishmanial effect of Commiphora wightii- Guggul and amphotericin B on a clinical isolate of Leishmania donovani (vol 223, 103800, 2020) - Routaray, Chinmayee Bar; Bhor, Renuka; Bai, Shakuntala; Kadam, Nitin Suryakant; Jagtap, Surabhi; Doshi, Pooja Jignesh; Sundar, Shyam; Sawant, Sangeeta; Kulkarni, Mahesh J.; Pai, Kalpana (Journal of Proteomics, 2021)
Drug resistance and relapse after treatment of visceral leishmaniasis (VL) with the chemotherapeutic drugs has impeded the VL elimination programme especially, in the endemic region of Bihar, India. Currently, Antimonials (Sbv) have been rendered obsolete (Bihar) as frequent treatment failure and relapse in Sbv treated patient's warrants greater vigilance and attention to the limited drugs. A clinical isolate of L.donovani obtained from an Amphotericin B (AmB) relapse patient was evaluated for its susceptibility to AmB and a hyperlipidemic drug Guggul. The evaluation of susceptibility or resistance to any drug still relies on in vitro assay on promastigote and amastigote stages of Leishmania spp. as there are no validated markers which can ascertain drug resistance in Leishmania. The anti-promastigote effect of AmB and Guggul were demonstrated by significant cellular and morphological changes exhibiting apoptosis-mediated cell death. To further illustrate the molecular mechanism of the parasite's response upon exposure to either AmB and Guggul, sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS) for quantitative proteomics analysis was performed along with computational data analysis; revealing considerable differences in the proteome profiles which could be regarded as putative markers for resistance or drug targets for development of therapeutic antileishmanials.